The Influence of the Project Based Learning (PjBL) Model on Student Learning Outcomes - Namira, Hafifah; Zuhdi, Muhammad; Wahyudi, Wahyudi (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
The purpose of the research to determine the effect of Project Based Learning (PjBL) model on student learning outcomes in optical instruments. The sampling technique used purposive sampling, obtained class XI MIPA 4 as experimental class and XI MIPA 5 as control class. The research design used was a nonequivalent control group design. The experimental class will be given treatment using the Project Based Learning (PjBL) model, while the control class will use the expository model (conventional learning). Learning outcomes abilities measured in the cognitive domain include: C1) remembering, C2) understanding, C3) applying, C4) analyzing, C5) evaluating, and C6) creating. The instrument used was 10 multiple choice questions. Data were analyzed using parametric statistics, namely Manova. The results showed a sinificance value of 0.000 < 0.05 and a value of Rcount > Rtable where 0.359 > 0.350, so H0 was rejected and Ha was accepted. So can be concluded that there is an influence of the Project Based Learning (PjBL) model on scientific literacy and student learning outcomes in optical equipment material.